A comparison of Canadian and American offender stereotypes - Allison, Meredith; Sweeney, Laura; Jung, Sandy (My University, 2013)
Offender stereotypes of Canadians and Americans were compared via an inductive, open-ended method. Participants were asked to write down the race, gender, and age for eleven types of offenders. There was agreement between the two countries in terms of race (White for eight offender types), gender (male for eight offenders), and age (similar estimation of age for six offenders). However, Americans were more likely to state that the Armed Robber was Black. Participants in both countries indicated that the Drug Trafficker was Black, although, a third of Americans also indicated this offender type was Hispanic. The findings are discussed in relation to the demographic makeup of the general, and offender populations of each country.